The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1081/iph-200051294
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide Attenuates Endotoxin- and Staphylococcal Exotoxin-Induced T-Cell Proliferation and Production of Cytokines and Chemokines

Abstract: Proinflammatory cytokines mediate the toxic effects of superantigenic staphylococcal exotoxins (SE) and bacterial lipopolysaccharide (LPS). Triptolide, an oxygenated diterpene derived from a traditional Chinese medicinal herb, Tripterygium wilfordii, inhibited SE-stimulated T-cell proliferation (by 98%) and expression of interleukin 1b, interleukin 6, tumor necrosis factor, gamma interferon, monocyte chemotactic protein 1, macrophage inflammatory protein (MIP)-1a, and MIP-1b by human peripheral blood mononucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 7 publications
3
21
0
Order By: Relevance
“…Coincident with our results, Lu et al found that triptolide inhibited the expression of MCP-1 in corneal fibroblasts induced by the proinflammatory cytokines IL-1β or TNF-α in a dose-dependent manner at both mRNA and protein levels [29]. Krakauer et al demonstrated that triptolide blocked the production of MCP-1 and MIP-1α by staphylococcal toxic shock syndrome toxin 1-and bacterial lipopolysaccharidestimulated human PBMC in a dose-dependent manner at both mRNA and protein levels [30]. Liu et al also found that triptolide inhibited LPS-induced DC production of MIP-1α, MCP-1, and RANTES at both mRNA and protein levels [31].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Coincident with our results, Lu et al found that triptolide inhibited the expression of MCP-1 in corneal fibroblasts induced by the proinflammatory cytokines IL-1β or TNF-α in a dose-dependent manner at both mRNA and protein levels [29]. Krakauer et al demonstrated that triptolide blocked the production of MCP-1 and MIP-1α by staphylococcal toxic shock syndrome toxin 1-and bacterial lipopolysaccharidestimulated human PBMC in a dose-dependent manner at both mRNA and protein levels [30]. Liu et al also found that triptolide inhibited LPS-induced DC production of MIP-1α, MCP-1, and RANTES at both mRNA and protein levels [31].…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies showed triptolide inhibited nuclear translocation and the formation of the NF-κB complex [32]. Triptolide can attenuate gene expression of TNF-α, IL-1β by murine peritoneal macrophages [33] or human PBMC [30] by inhibition of nuclear NF-κB activation. Therefore, chemokines expression is inhibited subsequently.…”
Section: Discussionmentioning
confidence: 96%
“…Many triterpene, diterpene and macrocyclic alkaloids have been isolated from this herb (Brinker et al, 2007;Ma et al, 2007). The most noteworthy component is triptolide, which has been reported to have significant antiinflammatory, immunomodulatory Krakauer et al, 2005;Liacini et al, 2005), antineoplastic (Jiang et al, 2001;Antonoff et al, 2009), and antiangiogenic properties (He et al, 2009Zhu et al, 2010). Two clinical trials in the US have shown very encouraging results (Tao et al, 2001(Tao et al, , 2002Goldbach-Mansky et al, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…Triptolide can inhibit PMA, TNF-α, or IL-1β-stimulated IL-6 and IL-8 expression by normal and transformed human bronchial epithelial cell [1], and inhibit SE-stimulated T-cell proliferation and expression of IL-1β, IL-6, TNF, IFN-γ, MCP-1, MIP-1α and MIP-1β by human PBMC [2]. Similar to human corneal fibroblasts, triptolide significantly inhibits LPS-induced expression of IL-6, G-CSF, MCP-1, IL-8, and ICAM-1 [3].…”
Section: Triptolide Inhibits Pro-inflammatory Cytokine and Chemokine mentioning
confidence: 99%